Pinocchio - Collodi, Carlo 1826-1890; Collodi, Carlo 1826-1890; Daly-Weir, Catherine (Bullseye step into classics, 1996)
Pinocchio, a wooden puppet full of tricks and mischief, with a talent for getting into and out of trouble, wants more than anything else to become a real boy.